10 Myr evolution of sedimentation rates in a deep marine to non‐marine foreland basin system: Tectonic and sedimentary controls (Eocene, Tremp–Jaca Basin, Southern Pyrenees, NE Spain). (4th August 2020) - Vinyoles, Andreu; López‐Blanco, Miguel; Garcés, Miguel; Arbués, Pau; Valero, Luis; Beamud, Elisabet; Oliva‐Urcia, Belén; Cabello, Patricia
Abstract: The propagation of the deformation front in foreland systems is typically accompanied by the incorporation of parts of the basin into wedge‐top piggy‐back basins, this process is likely producing considerable changes to sedimentation rates (SR). Here we investigate the spatial‐temporal evolution of SR for the Tremp–Jaca Basin in the Southern Pyrenees during its evolution from a wedge‐top, foreredeep, forebulge configuration to a wedge‐top stage. SR were controlled by a series of tectonic structures that influenced subsidence distribution and modified the sediment dispersal patterns. We compare the decompacted SR calculated from 12 magnetostratigraphic sections located throughout the Tremp–Jaca Basin represent the full range of depositional environment and times. While the derived long‐term SR range between 9.0 and 84.5 cm/kyr, compiled data at the scale of magnetozones (0.1–2.5 Myr) yield SR that range from 3.0 to 170 cm/kyr. From this analysis, three main types of depocenter are recognized: a regional depocenter in the foredeep depozone; depocenters related to both regional subsidence and salt tectonics in the wedge‐top depozone; and a depocenter related to clastic shelf building showing transgressive and regressive trends with graded and non‐graded episodes. From the evolution of SR we distinguish two stages. The Lutetian Stage (from 49.1–41.2 Ma) portrays a compartmentalized basin characterized by variable SR in dominantly underfilled accommodation areas. The markedly different advance of the deformation front between the Central and Western Pyrenees resulted in a complex distribution of the foreland depozones during this stage. The Bartonian–Priabonian Stage (41.2–36.9 Ma) represents the integration of the whole basin into the wedge‐top, showing a generalized reduction of SR in a mostly overfilled relatively uniform basin. The stacking of basement units in the hinterland during the whole period produced unusually high SR in the wedge‐top depozone. Abstract : The study of 10 Myr evolution of sedimentation rates on a Foreland Basin Systemhas demonstrated the effect of tectonic evolution and overfilled versus underfilled accommodation zones in the basin.